Cognitive abilities and precision in skiers and soccer players - Joksimovic, D.; Joksimovic, A.; Stankovic, D.; Hadzic, R. (Acta Kinesiologica, 2011)
The aim of this paper was to investigate the relations and differences in cognitive abilities and precision in skiers and soccer players. Research was performed on a sample of 45 elite young soccer players and elite skiers (30 soccer players and 15 skiers from the Serbian national teams) aged 13.88 ± 0.60 years. The following measuring instruments for the estimation of cognitive abilities were applied: perceptive speed, ability of analytical reasoning on a perceptive material and perceptive differentiation and logical reasoning; also three tests for the estimation of precision were used: hand aiming at the horizontal target, leg aiming at the vertical target and picado. Differences were investigated by t-test, while relations were investigated by canonic correlational analysis. Results point out to the fact that there is statistically significant difference between skiers and soccer players in all three tests of the cognitive abilities in favor of skiers, while in tests of precision statistically significant difference was obtained on most of applied tests. Analysis of corresponding canonic functions point to the assumption that success in precision of skiers and soccer players depends mostly on perceptive speed and perceptive differentiation and logical reasoning.